Utilization of Instagram @kominfodiy as Publication and Information Media for the Department of Communications and Informatics of the Special Region of Yogyakarta - Harsyid, Ahmad Ridho; Lestari, Rani Dwi; Awola, Eunike Dina (PT FORMOSA CENDEKIA GLOBAL, 2025)
The study used the Circular Model Of Some theory from Regina Luttrel which explains planning in using social media using 4 stages, namely share, manage, optimize and engage. From the data found, the DIY Communication and Information Office utilizes Instagram features as well as possible by distributing quality information and educational content, approaching followers in a responsive and responsive manner and having transparency to the community, approaching followers with the call